Efficacy and Characteristics of the Stimuli of Action Observation Therapy in Subjects With Parkinson's Disease: A Systematic Review - Temporiti, Federico; Adamo, Paola; Cavalli, Emanuele; Gatti, Roberto (Frontiers in Neurology, 2020)
Background. The discovery of the Mirror Neuron System has promoted the development of Action Observation Therapy (AOT) to improve motor and functional abilities in patients with Parkinson’s disease (PD). This innovative approach involves observing video-clips showing motor contents, which may vary across the studies influencing AOT efficacy. To date, no studies have systematically summarised the effects of AOT in patients with PD on motor and functional outcomes, underlining the characteristics of visual stimuli in relation to their efficacy. Objectives. To describe the potential benefits of AOT in patients with PD and discuss the characteristics of visual stimuli used in clinical studies in relation to their efficacy. Methods. A systematic literature search was carried out using MEDLINE via PubMed, EMBASE, Scopus and PEDro, from inception until March 2020. Randomized controlled trials that investigated the effects of AOT on motor and functional recovery in patients with PD were included. Two independent reviewers appraised the records for inclusion, assessed the methodological quality and extracted the following data: number and characteristics of participants, features and posology of the treatments, outcome measures at each follow-up and main results. Findings were aggregated into a quantitative synthesis (mean difference and 95% confidence interval) for each time-point. Results. Overall, 7 studies (189 participants) with a mean PEDro score of 6.1 (range: 4-8) points were selected. Included studies revealed AOT as effective in improving walking ability and typical motor signs (i.e. freezing of gait and bradykinesia) in patients with PD. Moreover, when this approach incorporated ecological auditory stimuli, changes to functional abilities and quality of life were also induced, which persisted up to 3 months after treatment. However, included studies adopted AOT stimuli with heterogeneous posology (from a single session to 8 weeks) and characteristics of motor contents might be responsible for different motor and functional recovery (person-related and viewing perspectives, transitive or intransitive actions, healthy subjects or patients and association or not with imitation). Conclusions. AOT leads to improvements in motor and functional abilities in patients with PD and the characteristics of visual stimuli may play a role in determining AOT effects, deserving further investigations.